2021
DOI: 10.28991/cej-2021-03091771
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Soil Stabilization Relevant to Transport Infrastructure using Bagasse Ash and Stone Dust and Cost Effectiveness

Abstract: Soft ground improvement to provide stable foundations for infrastructure is national priority for most countries. Weak soil may initiate instability to foundations reducing their lifespan, which necessitates the adoption of a suitable soil stabilization method. Amongst various soil stabilization techniques, using appropriate admixtures is quite popular. The present study aims to investigate the suitability of bagasse ash and stone dust as the admixtures for stabilizing soft clay, in terms of compaction and pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The breach channel slope for both soils becomes gentler during the progressive erosion of the upstream slope and gradually remains constant throughout the breach failure. Similar to the results of previous studies [35,36], down cutting of the breach channel and high erosion occurring near the sides of the breach entrance result in a severely undercut breach channel entrance. Undermining of the saturated dike slope in E4 is fast due to the high water turbulence in porous sand materials.…”
Section: Figure 21 Comparison Of Fos Between E4 and E6 Using Lemsupporting
confidence: 90%
“…The breach channel slope for both soils becomes gentler during the progressive erosion of the upstream slope and gradually remains constant throughout the breach failure. Similar to the results of previous studies [35,36], down cutting of the breach channel and high erosion occurring near the sides of the breach entrance result in a severely undercut breach channel entrance. Undermining of the saturated dike slope in E4 is fast due to the high water turbulence in porous sand materials.…”
Section: Figure 21 Comparison Of Fos Between E4 and E6 Using Lemsupporting
confidence: 90%
“…Researchers found that variations in compaction energy had a major effect on both swell potential and swelling pressure. Basack et al (2021) [36] researched the impact of various compaction energies on compaction parameters, UCS, CBR, and soil swell%. When compaction energy went up, MDD increased, OMC decreased, UCS increased, and CBR increased.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical stabilisation is also carried out by mixing or blending soils with two or more grain sizes to obtain a material that meets the required specifications. The focus of these methods is on changing the physical structure of the soil through compaction, mixing, or other mechanical techniques (Afrin, 2017;Archibong et al, 2020;Basack et al, 2021).…”
Section: Mechanical Soil Stabilisation Methodsmentioning
confidence: 99%
“…Chemical soil stabilisation is a method of improving soil properties through the introduction of chemical agents that interact with soil particles, changing their behavior and improving overall stability. Common chemical soil stabilisation methods include bitumen stabilisation, cement stabilisation, fly ash stabilisation, and lime stabilisation (Afrin, 2017;Archibong et al, 2020;Basack et al, 2021;Hasyimi & Syahril, 2021;Kuswaya et al, 2018;Rahman et al, 2019;Tan et al, 2020).…”
Section: Chemical Soil Stabilisation Methodsmentioning
confidence: 99%